227k views
0 votes
535 3+X +4 X-218(x + 4)(x-2)

User Kobra
by
5.9k points

1 Answer

6 votes

The first step is to multiply both sides of the equation by (x + 4)(x - 2)

It becomes


\begin{gathered} \frac{5(x\text{ + 4)(x - 2)}}{(x\text{ + 4)}}\text{ + }\frac{3(x\text{ + 4)(x - 2)}}{(x\text{ - 2)}}\text{ = }\frac{18(x\text{ + 4)(x - 2)}}{(x\text{ + 4)(x - 2)}} \\ 5(x\text{ - 2) + 3(x + 4) = 18} \\ 5x\text{ - 10 + 3x + 12 = 18} \\ 5x\text{ + 3x = 18 - 12 + 10} \\ 8x\text{ = 16} \\ x\text{ = }(16)/(8) \\ x\text{ = 2} \end{gathered}

User Zunan
by
5.6k points